Reformulasi Kurikulum Pesantren Dalam Rangka Meningkatkan Kwalitas Pendidikan Di Pondok Pesantren - fudholi Fudholi (LP2M IAI Miftahul Ulum Pamekasan, 2015)
Islamic boarding school is one of Islamic educational institutes existed during the Dutch colonization era and a place for Muslim cadre’s improvement spread out in the line of society. The existence of Islamic boarding school becomes a fortification of Muslim from any circumstances and condition faced by Indonesian, during the colonization era up to now. The intricacies of struggle done by all of alumnus from struggle of divesting from the hegemony of colonization, establishing revolution, forming a sovereign government carrying infrastructures out till finally participating in conducting a reformation. Now day’s Islamic boarding schools are demanded to revamp. One of things becoming attention is the curriculum used in Islamic boarding school. All this time, curriculum oriented by parts of Islamic boarding school is still about religious knowledge and salaf holly books. Parts of the owners of boarding school are still tendentious in defending or orienting back to the past methods (salaf). They have not felt yet about the needs of Islamic boarding school improvement by putting non-religious materials into the Islamic boarding school curriculum. Based on the explanation above, thus it is formulated how is the formula of Islamic boarding school curriculum improvement as an alternative of educational quality enhancement in Islamic boarding school and how is the system and action of curriculum development of Islamic boarding school in increasing the quality of its education. In general, the factors becoming a background of enhancing curriculum in Islamic boarding school can be grouped into two factors, internal and external factors. Internal factors cover, (a) the initiation of the owners to increase the quality of student’s knowledge. (b) the wish of Islamic boarding school owners to increase the efficiency and effectiveness of teaching in Islamic boarding school (c) the wish for alumnus to be ready of action in society. Meanwhile, the external factors are (a) the development of science and technology. (b). the influence of educational system dynamics (c). the demand of society and alumnus. The development implementation of curriculum of Islamic boarding school covers some principal components; these are component, purpose, material, strategy, and evaluation.